1999
DOI: 10.1016/s0378-1097(99)00293-1
|View full text |Cite
|
Sign up to set email alerts
|

The Tol proteins of Escherichia coli and their involvement in the uptake of biomolecules and outer membrane stability

Abstract: The Tol proteins of Escherichia coli are involved in outer membrane stability. They are also required for the uptake of the group A colicins and the translocation of filamentous phage DNA into the cytoplasm. The tol-pal genes constitute two operons in the E. coli genome, orf1tolQRA and tolBpalorf2. The TolQ TolR TolA proteins form a complex in the cytoplasmic membrane, while TolB and Pal interact near the outer membrane. Most of the amino acid residues of TolA, TolB, TolR and Pal are localized in the periplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 25 publications
6
76
1
Order By: Relevance
“…Unlike TonB, which interacts with the Ton-boxcontaining OM receptors, the C-terminal domain of TolA interacts with a periplasmic protein, TolB, or the OM lipoprotein PAL (384). Defects in any of the TolQR-TolB system components result in profound functional problems with the OM barrier, increasing drastically the formation of OM vesicles (see below), causing periplasmic proteins (such as RNase and ␤-lactamase) to leak out of the cell, and making the cells hypersusceptible to various noxious agents (367). The hypersusceptibility pattern is interesting in that it includes not only lipophilic agents expected to traverse the OM bilayer (such as SDS and cholate) (367) but also vancomycin (119), which is large but hydrophilic, so that it does not cross the OM unless large, supramolecular defects open up.…”
Section: Alterations Of the Om Bilayer Barriermentioning
confidence: 99%
“…Unlike TonB, which interacts with the Ton-boxcontaining OM receptors, the C-terminal domain of TolA interacts with a periplasmic protein, TolB, or the OM lipoprotein PAL (384). Defects in any of the TolQR-TolB system components result in profound functional problems with the OM barrier, increasing drastically the formation of OM vesicles (see below), causing periplasmic proteins (such as RNase and ␤-lactamase) to leak out of the cell, and making the cells hypersusceptible to various noxious agents (367). The hypersusceptibility pattern is interesting in that it includes not only lipophilic agents expected to traverse the OM bilayer (such as SDS and cholate) (367) but also vancomycin (119), which is large but hydrophilic, so that it does not cross the OM unless large, supramolecular defects open up.…”
Section: Alterations Of the Om Bilayer Barriermentioning
confidence: 99%
“…This system has also been found to facilitate the uptake of filamentous phage DNA and group A colicins. No obvious phenotypes have been assigned to ybgC and ybgF, which encode cytoplasmic and periplasmic proteins, respectively (Lazzaroni et al, 1999;Cascales & Lloubes, 2004). Recently, it has been shown that the TolA protein is required for the correct surface expression of the E. coli O7 antigen, thus demonstrating a role of the Tol-Pal system in LPS Fig.…”
Section: Members Of the S E Regulon Specific For S Typhimuriummentioning
confidence: 99%
“…The Tol-Pal system of Gram-negative bacteria is required for outer-membrane stability (Lazzaroni et al, 1999). It comprises five envelope proteins, TolQ, TolR, TolA, TolB and Pal, which form two complexes.…”
Section: Introductionmentioning
confidence: 99%